Some Problems of Inadmissible Applications under the Council Directive 2005/85/EC - Pazderová, Věra; Jílek, Dalibor, 1953-; Masarykova univerzita. Katedra mezinárodního a evropského práva (2007)
Předmětem této diplomové práce je analýza čl. 25 Procedurální směrnice (Směrnice Rady 2005/85/ES), který obsahuje důvody, pro které může být žádost o azyl prohlášena za nepřípustnou. Tyto důvody jsou zkoumány ve světle práva být chráněn před refoulement a práva na azyl. Cílem této práce je formulovat doporučení pro členské státy naznačující, zda tyto důvody pro nepřípustnost, které nabízí komunitární právo, mohou být bez obav transponovány, nebo zda-li by naopak mohlo dojít k porušení závazků členských států vyplývajících z mezinárodního a/nebo primárního evropského práva.
This thesis aims to examine whether a Member State may hold an application for asylum inadmissible for the reasons stated in Article 25 of the Procedures Directive (Council Directive 2005/85/EC). More specifically, the individual provisions of Article 25 are tested against both the right to be protected against refoulement and the right to asylum. The outcome of this analysis is intended as a recommendation to Member States indicating which of these grounds may be implemented into their national legal orders and which would entail non-compliance with their commitments.
Vedoucí práce: Dalibor Jílek.
Diplomová práce (Mgr.)--Masarykova univerzita, Právnická fakulta, 2007.
Keywords: mezinárodní právo; právo azylu; international law; right of asylum; diplomové práce